Using Big Data to Demonstrate Indivisibility of Rights and Promote Cross-Sectoral Responses to the Sustainable Development Goals. (5th May 2019) - Williams, Carmel; Exeter, Daniel; Gibb, Sheree; Hunt, Paul
Abstract: In this research we explore the meaning of the indivisibility of human rights in the context of the Sustainable Development Goals (SDGs). We draw on Big Data, using integrated administrative data sets and mapping of social deprivation in New Zealand, to explore the uptake of a 'free' health service for children. The data show that people living with multiple deprivations are less likely to take advantage of health checks for their children than people with fewer deprivations. This suggests that in order to improve child health, action is required across various social domains to address the multiple hardships that limit people's capacity to access health care; simply making a health service more available is an inadequate policy response. Viewed as a matter of human rights, these findings are a practical demonstration of the indivisibility of human rights: the right to health cannot be fulfilled when other social rights (information, education, housing, adequate standard of living, and nutrition) are unfulfilled. In the context of the SDGs and health, achieving SDG 3.8 (universal health care) similarly depends on the other SDG targets being met. This leads us to suggest that in well resourced settings, Big Data could enhance SDG accountability mechanisms by providing a consistent focus across all SDG targets on the same group of people in any country: those who are left behind. Consistent reporting on this group keeps the focus on people rather than technocratic goals, and helps demonstrate that improving one social right, such as health, requires improvement of all other social rights.